2020
DOI: 10.48550/arxiv.2008.01985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hawking--Page phase transitions in four-dimensional Einstein--Gauss--Bonnet gravity

Abstract: The Hawking-Page (HP) phase transitions of the anti-de Sitter black holes in the extended phase space are studied in a novel four-dimensional Einstein-Gauss-Bonnet (4EGB) gravity, which is proposed by rescaling the Gauss-Bonnet (GB) coupling constant α → α/(d − 4) in d dimensions and redefining the four-dimensional gravity in the limit d → 4. The GB term shows nontrivial contributions to both black hole mass and entropy simultaneously, and decreases the HP phase transition temperature THP. Moreover, the HP pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 68 publications
(74 reference statements)
0
18
0
Order By: Relevance
“…As discussed, the canonical ensemble consists of a series of black hole spacetimes with arbitrary radius. The probability distribution of these black hole states ρ(r, t), which is a function of the black hole radius r and time t, satisfies the Fokker-Planck equation on the free energy landscape [23,[28][29][30][31] ∂ρ(r, t) ∂t = D ∂ ∂r e −βG(r) ∂ ∂r e βG(r) ρ(r, t) , (18) where β = 1/kT is the inverse temperature and D = kT /ζ is the diffusion coefficient with k being the Boltzman constant and ζ being dissipation coefficient. We take k = ζ = 1 without loss of generality.…”
Section: B Probabilistic Evolution On the Free Energy Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…As discussed, the canonical ensemble consists of a series of black hole spacetimes with arbitrary radius. The probability distribution of these black hole states ρ(r, t), which is a function of the black hole radius r and time t, satisfies the Fokker-Planck equation on the free energy landscape [23,[28][29][30][31] ∂ρ(r, t) ∂t = D ∂ ∂r e −βG(r) ∂ ∂r e βG(r) ρ(r, t) , (18) where β = 1/kT is the inverse temperature and D = kT /ζ is the diffusion coefficient with k being the Boltzman constant and ζ being dissipation coefficient. We take k = ζ = 1 without loss of generality.…”
Section: B Probabilistic Evolution On the Free Energy Landscapementioning
confidence: 99%
“…In [10], the vacuum solution found by Glavan and Lin in [1] was generalized to be charged in AdS space. Then, the thermodynamics and phase transitions in extended phase space, where the cosmological constant is taken as the thermodynamic pressure, was studied in [11][12][13][14][15][16][17][18][19]. Especially, it is shown in [14] that there exists the small-large black hole phase transition both in the canonical ensemble and in the grand canonical ensemble, which has an analogy of the van der Walls liquid-gas phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…The Hawking-Page phase transition has been widely studied in the literature from holography to modified gravity theories [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. In general, these studies are based on the assumption that black holes can be treated as the thermodynamic entities.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of the theory is widely investigated in the literature, exploring its effects in black-holes [10], wormholes [11], compact stars [12] and also in cosmology [13]. Also, many works has been done to generalize the idea to higher/lower dimensions, relations to other theories and also its quantum aspects of the theory [14]. For example, in [15], the authors showed that in order to have a well-defined linearized theory the metric should be locally conformally flat.…”
Section: Introductionmentioning
confidence: 99%